Analysis of Climatic Basis for the Change of Cultivated Land Area in Sanjiang Plain of China - Zhang, Luyang; Wang, Zhaolin; E, Shixuan; Du, Guoming; Chen, Zhushu (Frontiers in Earth Science, 2022)
As the research area of this study, Sanjiang Plain is an important grain producing area and commodity grain base in China, which plays an important role in China's food security and stability. From 2000 to 2015, the climatic conditions and cultivated land use in this region changed significantly. The climatic basis for the changes occuring to the regional cultivated land use area was revealed using several analytical methods such as correlation coefficient and geographic detector. The findings are as follows: (1) The internal changes of cultivated land use were mainly from dry land changed to paddy field, and the area ratio of dry land to paddy field gradually decreased from 3.80: 1 to 1.19: 1. (2) The average air temperature and precipitation during the tillage period were 18.05℃ and 428.25mm, respectively. (3) The long-term increasing temperature trend promotes the transformation from dry land to paddy fields, but the increase in June precipitation inhibits it. (4) Regional hydrothermal climatic factors can go some way to explaining the cultivated land use spatial distribution. The trends of two factors are interlinked, and together explain the changes more effectively than when just considering individual factors.